2021
DOI: 10.1038/s41598-021-89351-9
|View full text |Cite|
|
Sign up to set email alerts
|

Experimentally and theoretically approaches for disperse red 60 dye adsorption on novel quaternary nanocomposites

Abstract: A comprehensive study that combined both experimental and computational experiments was performed to evaluate the usage of organo-metal oxide nanocomposite for the elimination of disperse red 60 dye (DR) from aqueous solutions. Chitosan was modified by Schiff base to form nanoneedles chitosan-4-chloroacetophenone derivative. The derivatives were then impregnated with CeO2–CuO–Fe2O3 or CeO2–CuO–Al2O3 metal oxides to prepare a novel quarternary organo-metal oxide nanocomposite. The novel nanocomposite, chitosan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Various formulations of modified composites and various state-of-the-art techniques for the removal of dyes from wastewater have recently been proposed by numerous researchers [ 36 , 37 , 38 ]. Thus, new magnetic nanocomposites based on the Fe 3 O 4 magnetite were successfully obtained by combustion and tested as adsorbents for the removal of anionic dyes such as Acid Yellow 42 and Acid Red 213 from aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various formulations of modified composites and various state-of-the-art techniques for the removal of dyes from wastewater have recently been proposed by numerous researchers [ 36 , 37 , 38 ]. Thus, new magnetic nanocomposites based on the Fe 3 O 4 magnetite were successfully obtained by combustion and tested as adsorbents for the removal of anionic dyes such as Acid Yellow 42 and Acid Red 213 from aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive study was performed to evaluate the use of an organometallic oxide chitosan-4-chloroacetophenone/CeO 2 –CuO–Fe 2 O 3 and chitosan-4-chloroacetophenone/CeO 2 –CuO–Al 2 O 3 nanocomposites for the removal of Red 60 disperse dye (DR) from aqueous solutions. An analysis of the molecular structure of the DR dye adsorbed on the surface of these nanocomposites showed that the adsorption process is related to the van der Waals dispersion force [ 37 ]. Recently, various physicochemical and biological wastewater treatment processes have also been studied with various types of adsorbents, such as commercial activated carbon, metal oxide adsorbents, carbon adsorbents, organometallic frameworks, and polymer adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern presented in Figure 8 a suggests that the increasing MV concentration tends to reduce the removal efficiency of either adsorption or photooxidation by both Zn-Al LDHs and c-Zn-Al LDHs. In general, the intensive adsorption was achieved at low concentrations as the rapid removal was higher at an enormous number of available active adsorption spots on the material’s surface [ 31 ]. In more detail, the removal of around 90–100% was achieved at the initial concentration of 1–5 ppm over the photocatalysis process.…”
Section: Resultsmentioning
confidence: 99%
“…model is the model that judges the MB adsorption process. At 25 °C, the R 2 calculated by the Langmuir isotherms was 0.9878 For Langmuir adsorption isotherm, the R L value is less than one, meaning that MB adsorption is favourable under the current studied circumstances [70]. According to Langmuir adsorption isotherm, 53.4 mg/g is the maximum expected AC500/NZ's adsorption capacity.…”
Section: Number Of Runsmentioning
confidence: 88%